Doa Mengubah Segalanya Perspektif Jemaat ONKP Resort Sibolga - Sefriadi Beji Duhu Laia (Berkat : Jurnal Pendidikan Agama dan Katolik, 2025)
The purpose of this study was to determine the understanding of the ONKP Resort Sibolga congregation that prayer can change everything and to what extent the role of prayer changes everything. The research method is qualitative research. The data collection technique for this study was using semi-structured interviews. The data obtained were analyzed descriptively qualitatively. Based on the results of interviews with the ONKP Resort Sibolga congregation about prayer being able to change everything, the congregation believes and trusts that prayer can change everything. Prayer can change everything when the congregation has faith that the prayers offered must be full of confidence that the power of prayer will occur in their lives. The congregation also said that the prayers of the righteous will be realized by God. When people pray to accept Jesus Christ as Lord and Savior, then God automatically justifies the person. In addition, prayer can change everything when the congregation is obedient to the word of God. Obedience is proof that someone truly loves God. Disobedience is a rebellious attitude that God hates. God hears the prayers of those who are willing to obey the truth of the Bible, in other words disobedience is a barrier to answered prayer. (John 15:7). Prayer also has a role in calming the anxiety experienced by the congregation.